Peculiarities of the self-presentation of preschool children - Inna Zhuravleva (Problemy Wczesnej Edukacji)
The results of a study on self-presentation in the light of the history of mankind and culture are presented. A definition of self-presentation as a phenomenon closely related to child development is given. The peculiarities of self-presentation are shown by an analysis of the structure of preschoolers’ self-consciousness. A typology of preschool children’s self-presentation is presented.